Circulating Leptin and Risk of Pancreatic Cancer: A Pooled Analysis From 3 Cohorts - Stolzenberg-Solomon, Rachael Z. (Am J Epidemiol, 2015)
Adiposity is associated with pancreatic cancer; however, the underlying mechanism(s) is uncertain. Leptin is an adipokine involved in metabolic regulation, and obese individuals have higher concentrations. We conducted a pooled, nested case-control study of cohort participants from the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial, the Alpha-Tocopherol, Beta-Carotene Cancer Prevention Study, and the Cancer Prevention Study II Nutrition Cohort to investigate whether prediagnostic serum leptin was associated with pancreatic cancer. A total of 731 pancreatic adenocarcinoma cases that occurred between 1986 and 2010 were included (maximum follow-up, 23 years). Incidence density–selected controls (n = 909) were matched to cases by cohort, age, sex, race, and blood draw date. Conditional logistic regression was used to calculate odds ratios and 95% confidence intervals. Sex-specific quintiles were based on the distribution of the controls. Overall, serum leptin was not associated with pancreatic cancer (quintile 5 vs. quintile 1: odds ratio = 1.13, 95% confidence interval: 0.75, 1.71; P(trend) = 0.38). There was a significant interaction by follow-up time (P = 0.003), such that elevated risk was apparent only during follow-up of more than 10 years after blood draw (quintile 5 vs. quintile 1: odds ratio = 2.55, 95% confidence interval: 1.23, 5.27; P(trend) = 0.004). Our results support an association between increasing leptin concentration and pancreatic cancer; however, long follow-up is necessary to observe the relationship. Subclinical disease may explain the lack of association during early follow-up.